El tiempo no conceptual en Los Recuerdos del Porvenir de Elena Garro - Villaseñor Ramírez, Isolda (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
The memories of the Future are the writer's poplin more important novel Elena Garr (1917-1998). Although written ten years before, it was published in 1963 and it has been considered as one of the literary most important jewels in the Mexican letters. Elena wrote theater, poetry, story, novelizes and he/she made journalism, and its work has been studied from different and very varied perspectives, that which reveals their wealth. Sometimes considered as part of the literature of the magic realism, feminist or as a literature type that treats the topic of the Mexican Revolution and eventual Guerra Crist era like a resource for the purification, reparation or digestion of this events, the work of Garr goes beyond all these determinations that, for example, Lopátegui considers in relation to the determination of the it works as magic realism, it is about an easy resource that doesn't allow to see the complexity of the work; in interview with Carlos Landeros was own Elena who being compared with the intellectual great feminist Simone of Beauvoire, refuses flatly to be a feminist herself, that which you/they have also observed some of their critics, for example, Ignacio Sánchez considers it like a writer more than feminist that sits down the bases for those gender studies inside the Mexican literature.

Los recuerdos del Porvenir es la novela más importante de la escritora poblana Elena Garro (1917-1998). Aunque escrita diez años antes, fue publicada en 1963 y ha sido considerada como una de las joyas literarias más importantes de las letras mexicanas. Elena escribió teatro, poesía, cuento, novela e hizo periodismo, y su obra ha sido estudiada desde distintas y muy variadas perspectivas, lo cual revela su riqueza. A veces considerada como parte de la literatura del realismo mágico, feminista o como un tipo de literatura que trata el tema de la Revolución Mexicana y la eventual Guerra Cristera como un recurso para la purificación, saneamiento o digestión de dichos eventos, la obra de Garro va más allá de todas estas determinaciones que, por ejemplo, Lopátegui considera en relación a la determinación de la obra como realismo mágico, se trata de un recurso fácil que no permite ver la complejidad de la obra; en entrevista con Carlos Landeros fue la propia Elena, quien comparándose con la gran feminista intelectual Simone de Beauvoire, niega rotundamente ser una feminista ella misma, lo cual también han observado algunos de sus críticos, por ejemplo, Ignacio Sánchez la considera como una escritora más que feminista, que sienta las bases para los estudios de género dentro de la literatura mexicana.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2009-0027; Naturaleza; Identidad; Porvenir; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/57